STATE OF INDIVIDUAL LABORATORY PARAMETERS AND PARAMETERS OF THE HEMOSTASIS SYSTEM IN CHILDREN WITH HEMOLYTIC-UREMIC SYNDROME - Галина Ивановна Выходцева; Евгения Юрьевна Киричек; Ольга Ивановна Колесникова; Елена Геннадьевна Махова; Людмила Михайловна Новикова; Евгений Васильевич Скударнов; Олеся Николаевна Зенченко (The Publishing House Medicine and Enlightenment, 2023)
Objective of the study. To evaluate the status of individual laboratory parameters and parameters of the hemostasis system in children with hemolytic-uremic syndrome (HUS) to assess the course of the pathological process. Materials and methods of investigation. An analysis of clinical and laboratory manifestations of typical HUS was performed based on 11 cases histories of children who were treated at the Altai Krai Clinical Center for Maternal and Child Health Care, a regional state budget-funded health care institution, for the period 2013-2018. All children during the period of observation underwent general clinical laboratory tests - general blood count, general urinalysis; biochemical blood count - free plasma hemoglobin, urea, creatinine, total bilirubin and fractions, LDH; study of individual parameters of vascular-platelet and coagulation links of hemostasis system. Statistical processing was performed using the software package Statistica Ver. 10.0 (StatSoft, Inc.). Results of the study. In the course of the study we focused on changes in individual laboratory indices and parameters of the hemostasis and homeostasis system. Namely: combination of severe anemia with increased free blood hemoglobin and high LDH level (sign of intravascular hemolysis in children with HUS and severity of course); reduced values of platelet count in combination with changes in vascular-platelet hemostasis in the form of weakened induced platelet aggregation (result of consumption of functionally active platelets during microthrombosis); pronounced and prolonged disorders of renal nitrogen excretion function; changes in the coagulation component of the hemostasis system (as a possible manifestation of DIC) requiring continued correction of blood rheology disorders in patients with high values of SFMCs by OFT. Conclusion. The course of HUS in children is accompanied by severe anemia and thrombocytopenia, increased free blood hemoglobin, as a consequence, pronounced and prolonged impairment of GFR and the development of ARF. Absence of reliable difference of APTT and CT indexes from control values on the 1st and on the 6th-7th days of the disease indicates the absence of consumption phase development on the average in the group during this observation period, which excludes possible development of the HUS terminal phase during this period, which requires further monitoring of the hemostasis system indexes in the same volume. The increase of SFMCs values by OFT as a sign of progressive thrombinemia in children with HUS is an indication for continued correction of blood rheology disorders.